2018
DOI: 10.1007/s10103-018-2456-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prior application with and without post-injury treatment with low-level laser on the modulation of key proteins in the muscle repair process

Abstract: The aim of the present study was to evaluate the effects of LLLT prior to muscle injury with and without post-injury irradiation on the expression of isoforms of myosin heavy chain (MyHC), calcineurin (CaN), and myostatin during the repair process. Wistar rats were divided into five groups: control (n = 7); injury (n = 21); LLLT + injury (n = 21); injury + LLLT (n = 21), and LLLT + injury + LLLT (n = 21). Cryoinjury was performed on the tibialis anterior (TA) muscle. The injured groups were euthanized at 3, 7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Experimental studies are fundamental to the assessment of the safety, effectiveness, and applicability of different therapeutic modalities. For the analysis of the muscle repair process in in vivo studies, the cryoinjury method is well established and has viable reproducibility [12,16,[22][23][24]27]. Moreover, this model mimics the response of a muscle regarding damage compatible with a contusion [14,43].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental studies are fundamental to the assessment of the safety, effectiveness, and applicability of different therapeutic modalities. For the analysis of the muscle repair process in in vivo studies, the cryoinjury method is well established and has viable reproducibility [12,16,[22][23][24]27]. Moreover, this model mimics the response of a muscle regarding damage compatible with a contusion [14,43].…”
Section: Discussionmentioning
confidence: 99%
“…Ribeiro et al [15] evaluated irradiation performed previous to the induction of injury alone and in combination with PMB performed after the induction of injury using the red and infrared spectra (660 and 780 nm, 10 J/ cm 2 per point, 40 mW, 3.2 J, total of 8 points), reporting that the wavelength of 780 nm led to a positive modulation of the activity of antioxidant enzymes and a reduction in markers of oxidative stress in the microenvironment 3 and 7 days after the muscle injury. Using the same total energy in the infrared spectrum (780 nm, 10 J/cm 2 per point, 40 mW, 3.2 J, total of 8 points), Rodrigues et al [16] found that PBM administered previously at the site of the injury promoted the modulation of myostatin, calcineurin, and myostatin heavy chains after 3 days. The parameters described in these studies involving PBM administered locally to the tibialis anterior muscle were the same as those employed in the present investigation (780 nm, total of 80 J/cm 2 , 40 mW, 3.2 J) and demonstrated similar positive effects in muscle repair, despite the different form of application (directly over the injury vs transcutaneously over the vascular bed).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autocrine and paracrine muscle-growth inhibition has previously been attributed to myostatin, which is a TGFβ family member that is most dominantly expressed in skeletal muscle [ 102 ]. TGFβ1 and myostatin are released by muscle cells to provide signaling cues for muscle regeneration [ 103 ].…”
Section: Commonalities and Differences In Healing Cascades Of Diffmentioning
confidence: 99%